Intermittent chylomicronemia caused by intermittent GPIHBP1 autoantibodies - Ashraf, Ambika P. (J Clin Lipidol, 2020)
Chylomicronemia caused by a deficiency in lipoprotein lipase (LPL) or GPIHBP1 (the endothelial cell protein that transports LPL to the capillary lumen) is typically diagnosed during childhood and represents a serious, lifelong medical problem. Affected patients have high plasma triglyceride levels (>1500 mg/dl) and a high risk of acute pancreatitis. However, chylomicronemia frequently presents later in life in the absence of an obvious monogenic cause. In these cases, the etiology for the chylomicronemia is presumed to be “multifactorial” (involving diabetes, drugs, alcohol, or polygenic factors) but on a practical level the underlying cause generally remains a mystery. Here, we describe a 15-year-old female with chylomicronemia caused by GPIHBP1 autoantibodies (which abolish LPL transport to the capillary lumen). Remarkably, chylomicronemia in this patient was intermittent, interspersed between periods when the plasma triglyceride levels were normal. GPIHBP1 autoantibodies were easily detectable during episodes of chylomicronemia but were undetectable during periods of normotriglyceridemia. During the episodes of chylomicronemia (when GPIHBP1 autoantibodies were present), plasma LPL levels were low, consistent with impaired LPL transport into capillaries. During periods of normotriglyceridemia, when GPIHBP1 autoantibodies were absent, plasma LPL levels normalized. Because the chylomicronemia in this patient was accompanied by debilitating episodes of acute pancreatitis, the patient was ultimately treated with immunosuppressive drugs, which resulted in disappearance of GPIHBP1 autoantibodies and normalization of plasma triglyceride levels. GPIHBP1 autoantibodies need to be considered in patients who present with unexplained acquired cases of chylomicronemia.